Longevity of small-scale ('baby') plumes and their role in lithospheric break-up. Issue 1 (9th June 2021) - Koptev, Alexander; Cloetingh, Sierd; Ehlers, Todd A
SUMMARY: Controversy between advocates of 'active' (plume-activated) versus 'passive' (driven by external tectonic stresses) modes of continental rifting and break-up has persisted for decades. To a large extent, inconsistencies between observations and models are rooted in the conceptual model of plumes as voluminous upwellings of hot material sourced from the deep mantle. Such large-scale plumes are expected to induce intensive magmatism and topographic uplift, thereby triggering rifting. In this case of an 'active' rifting-to-break-up system, emplacement of plume-related magmatism should precede the onset of rifting that is not observed in many rifted continental margins, thus providing a primary argument in favour of an antiplume origin for continental break-up and supercontinent fragmentation. However, mantle plumes are not restricted to whole-mantle ('primary') plumes emanating from the mantle-core boundary but also include 'secondary' plumes originating from the upper mantle transition zone or shallower. Over the last decades a number of such 'secondary' plumes with horizontal diameters of only ∼100–200 km (therefore, sometimes also called 'baby' plumes) have been imaged in the upper mantle below Europe and China. The longevity of such small-scale plumes and their impact on geodynamics of continental break-up have so far not been explored. We present results of a systematic parametrical analysis of relatively small thermal anomalies seeded at the base of the lithosphere. In particular, we explore the effects of variations in initial plume temperature ( T  = 1500–1700 °C) and size (diameter of 80–116 km), characteristics of the overlying lithosphere (e.g. 'Cratonic', 'Variscan', 'Mesozoic' and oceanic) and intraplate tectonic regimes (neutral or far-field extension of 2–10 mm yr –1 ). In tectonically neutral regimes, the expected decay time of a seismically detectable 'baby'-plume varies from ∼20 to >200 Myr and is mainly controlled by its initial size and temperature, whereas the effect of variations in the thermotectonic age of the overlying lithosphere is modest. These small but enduring plumes are able to trigger localized rifting and subsequent continental break-up occurring from ∼10 to >300 Myr after the onset of far-field extension. Regardless of the thermomechanical structure of the lithosphere, relatively rapid (tens of Myr) break-up (observed in models with a hot plume and fast extension) favours partial melting of plume material. In contrast, in the case of a long-lasting (a few hundreds of Myr) pre-break-up phase (relatively cold plume, low extension rate), rifting is accompanied by modest decompressional melting of only 'normal' sublithospheric mantle. On the basis of the models presented, we distinguish two additional modes of continental rifting and break-up: (1) 'semi-active' when syn-break-up magmatism is carrying geochemical signatures of the deep mantle with deformation localized above the plume head not anymore connected by its tail to the original source of hot material and (2) 'semi-passive' when the site of final lithospheric rupture is controlled by a thermal anomaly of plume origin but without invoking its syn-break-up melting. These intermediate mechanisms are applicable to several segments of the passive continental margins formed during Pangea fragmentation.